Transcription Factor Lbx1 Expression in Mouse Embryonic Stem Cell-Derived Phenotypes - Stefanie Schmitteckert; Cornelia Ziegler; Liane Kartes; Alexandra Rolletschek (Stem Cells International)
Transcription factor Lbx1 is known to play a role in the migration of muscle progenitor cells in limb buds and also in neuronal determination processes. In addition, involvement of Lbx1 in cardiac neural crest-related cardiogenesis was postulated. Here, we used mouse embryonic stem (ES) cells which have the capacity to develop into cells of all three primary germ layers. During in vitro differentiation, ES cells recapitulate cellular developmental processes and gene expression patterns of early embryogenesis. Transcript analysis revealed a significant upregulation of Lbx1 at the progenitor cell stage. Immunofluorescence staining confirmed the expression of Lbx1 in skeletal muscle cell progenitors and GABAergic neurons. To verify the presence of Lbx1 in cardiac cells, triple immunocytochemistry of ES cell-derived cardiomyocytes and a quantification assay were performed at different developmental stages. Colabeling of Lbx1 and cardiac specific markers troponin T, α-actinin, GATA4, and Nkx2.5 suggested a potential role in early myocardial development.